Pemerolehan Bahasa Anak Usia Dini: Studi Kasus pada Seorang Anak Usia 3-5 Tahun - Mayora Hutasoit, Trides; Enika Lingga, Yesna; Purba, Melani; Sari Manik, Adetha; Azizah, Nurul (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Children's language acquisition is a complex process involving the development of phonology, morphology, syntax, and semantics. This study aims to analyze the language development of children aged 3-5 years based on four observation reports involving children named Renata Sitorus, Sari Ramadani Nasution, and Anisa Zahra. With a qualitative descriptive approach, this study compares the development of phonology, morphology, syntax, and semantics in children in that age range. The results showed that as children get older, the language structures they master become more complex. Phonological errors are common in children aged 3 years, while syntax develops better at age 5 years. A formula for the speed of language acquisition was developed based on the amount of understanding and sentence structure used by children. This study provides insight into the factors that influence children's language development and optimal language stimulation strategies.